Characterization of Tonsilloliths in Cone Beam Computed Tomography Scans of Patients Treated at the Teaching Dental Center of Universidad Peruana Cayetano Heredia, Lima, Peru, 2018-2021 - Cavero Aguirre, Alex Eduardo (2023)
The origin of tonsilloliths is related to a history of recurring tonsillitis or tonsillar abscesses during childhood. This study investigates the frequency, number, location, size, shape, as well as the age and sex of the patients, in order to establish parameters for the characteristics and statistical data that contribute to the early detection of this condition. Objective: To determine the characteristics of tonsilloliths in cone beam computed tomography (CBCT) scans of patients treated at the Teaching Dental Center of Universidad Peruana Cayetano Heredia. Material and methods: An observational, descriptive, retrospective, cross-sectional study was conducted, analyzing all CBCT scans from the period 2018-2021. Out of the total scans, 200 met the selection criteria. The chi-square test was used to establish relationships between variables, with a 95% confidence interval and a significance level of 0.05. Results: Among the 200 CBCT scans analyzed, 49 (24.5 %) showed tonsilloliths. Among these, 39 (19.5 %) belonged to female patients, while 32 (16 %) were patients older than 50 years. A total of 21 (42.86 %) scans presented a single tonsillolith, and 30 (61.2%) were located unilaterally. The analysis revealed a total count of 124 tonsilloliths, with 64 (51.6%) located on the right side. Furthermore, 88 (71.96 %) of the tonsilloliths exhibited a punctiform shape, with an average size of 1.68 mm. Conclusions: Tonsilloliths demonstrated a high frequency, primarily among females from the fifth decade of life, with sizes less than 2 mm, predominantly punctiform in shape, and located unilaterally.